'Weighty Celebrity': Corpulency, Monstrosity, and Freakery in Eighteenth- and Nineteenth-Century England - Whitney Dirks (Disability Studies Quarterly, 2019)
Obesity seems to have become prevalent in English society in the eighteenth century, likely as a result of changes in the country's diet such as an increasing consumption of sugar. With the greater incidence of corpulence in the population came more fat individuals on England's lucrative show circuit, joining the conjoined twins, hermaphrodites, dwarfs, giants, and individuals of different ethnicities who had peopled London's pubs, coffee houses, and exhibition halls for centuries. This article contextualizes historical corpulency in terms of early modern monstrosity and nineteenth-century freakery, with additional input from the modern Fat Studies and Disability Studies movements, in order to explore public consciousness about and fascination with particularly obese individuals, epitomized by the fattest men of the eighteenth and nineteenth centuries: the 616-pound (279 kg) Edward Bright and the 739-pound (335 kg) Daniel Lambert. Using a variety of source materials—newspaper articles, dieting pamphlets, medical and scientific essays, advertising leaflets and etchings, and popular histories about the lives of famous individuals—this essay argues that, though extremely corpulent individuals needed to exist in the first place in order to be incorporated into the show circuit, it was society's fascination with these new, unusual bodies that allowed them to rise into prominence as an entertainment feature in eighteenth- and nineteenth-century England.
Keywords: corpulency; obesity; fat; disability; monstrosity; freakery; eighteenth century; nineteenth century; Britain; England